Dashiell Hammett and the movies - Mooney, William H., 1948- (Rutgers University Press, 2015)
As the father of the hardboiled detective genre, Dashiell Hammett had a huge influence on Hollywood. Yet, it is easy to forget how adaptable Hammett's work was, fitting into a variety of genres and inspiring generations of filmmakers. Dashiell Hammett and the Movies offers the first comprehensive look at Hammett's broad oeuvre and how it was adapted into films from the 1930s all the way into the 1990s. Film scholar William H. Mooney reveals the wide range of films crafted from the same Hammett novels, as when The Maltese Falcon was filmed first as a pre-Code sexploitation movie, then as a Bette.